Differences in Body Esteem and Sexual Assertiveness between Male and Female College Students (Medico Legal Update, 2021)
The present study was conducted to identify the differences in body esteem and sexual assertiveness betweenmale and female college students. A total of 288 students (156 males and 132 females) from a universityin Chungnam, South Korea, participated in this study. A self-administered questionnaire survey with thestudy participants was conducted from December 1 to 14, 2018. The data obtained were analyzed usingdescriptive statistics, c2 test, analysis of covariance, t test, one-way analysis of variance (Scheffé test forpost hoc analysis), and linear regression with the IBM SPSS 20.0 program. Body esteem among the malestudents was higher than that among the female students, whereas sexual assertiveness among the femalestudents was higher than that among the male students. Body esteem differed according to body imageperception in the male students and according to body image perception as well as the number of romanticrelationships in the female students. Sexual assertiveness differed according to grade level and body imageperception in the male students only. In all the study participants, the higher the body esteem, the higher thesexual assertiveness. These results indicate that (1) interventions that increase the body esteem of femalestudents should be provided and (2) interventions that increase sexual assertiveness should factor in bodyesteem. Additionally, developmental interventions for body esteem and sexual assertiveness should considerbody image perception.